2010
DOI: 10.1038/nchembio.371
|View full text |Cite
|
Sign up to set email alerts
|

Branched intermediate formation stimulates peptide bond cleavage in protein splicing

Abstract: Protein splicing is a posttranslational modification in which an intein domain excises itself out of a host protein. Here, we investigate how the steps in the splicing process are coordinated so as to maximize the production of the final splice products and minimize the generation of undesired cleavage products. Our approach has been to prepare a branched intermediate (and analogs thereof) of the Mxe GyrA intein using protein semi-synthesis. Kinetic analysis of these molecules indicates that the high fidelity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
97
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 39 publications
2
97
0
Order By: Relevance
“…This circumvented insurmountable synthetic problems (SI Appendix) associated with the preparation of the branched peptide containing both a backbone ester (at Val182) and a side-chain ester (connecting the exteins). Fortunately, we have previously shown that the rate of branched intermediate resolution is unaffected by the substitution of Dapa for the +1 Thr (15). Thus, we could assess the effect of the backbone amide-to-ester substitution at Val182 using this system.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…This circumvented insurmountable synthetic problems (SI Appendix) associated with the preparation of the branched peptide containing both a backbone ester (at Val182) and a side-chain ester (connecting the exteins). Fortunately, we have previously shown that the rate of branched intermediate resolution is unaffected by the substitution of Dapa for the +1 Thr (15). Thus, we could assess the effect of the backbone amide-to-ester substitution at Val182 using this system.…”
Section: Significancementioning
confidence: 99%
“…Mxe GyrA is the most commonly used intein in protein engineering applications (9). Solution NMR studies on this semisynthetic construct suggest that branched intermediate formation affects the local structure around the +1 scissile amide bond connecting the intein to the C-extein, whereas kinetic studies indicate that inteinsuccinimide formation is greatly stimulated in the context of this intermediate (15). These studies also suggest an approach to trap the branched structure for high-resolution structure studies, based on mutation of a key histidine residue in the intein, His187 within block F (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…The new results of Liu et al should be viewed in context of an earlier study, where this semisynthetic branched intermediate (ssBI) was first analyzed with solution NMR (10). Comparison of NMR spectra of the ssBI and the starting precursor indicated repositioning of some catalytic residues in the intein.…”
mentioning
confidence: 99%